Strengthening self-integrity through self-affirmation: An experimental study among double jeopardy students - Khan, Mobina; Beri, Nimisha (Journal of Interdisciplinary Studies in Education, 2026)
This study explores the effect of self-affirmation interventions on the self-integrity of middle school migrant girls facing double jeopardy. Using an experimental design, 64 eighth-grade girls from government schools in Jalandhar were selected through purposive sampling. Participants were grouped into experimental and control groups based on pretest scores using a Hindi self-integrity scale. The experimental group received three self-affirmation interventions at 58- and 55-day intervals. Posttests followed each session, with a final test 30 days after the last intervention. Initial results showed no immediate improvement, but later posttests revealed significant, lasting gains in the experimental group. The findings suggest that self-affirmation enhances self-integrity over time, offering a low-cost method to support disadvantaged students and help them resist stereotype threats in education.